Dopamine-dependent architecture of cortico-subcortical network connectivity. - Cole, D; Oei, N; Soeter, R; Both, S; van Gerven, J; Rombouts, SA; Beckmann, C (2013)
Maladaptive dopaminergic mediation of reward processing in humans is thought to underlie multiple neuropsychiatric disorders, including addiction, Parkinson's disease, and schizophrenia. Mechanisms responsible for the development of such disorders may depend on individual differences in neural signaling within large-scale cortico-subcortical circuitry. Using a combination of functional neuroimaging and pharmacological challenges in healthy volunteers, we identified opposing dopamine agonistic and antagonistic neuromodulatory effects on distributed functional interactions between specific subcortical regions and corresponding neocortical "resting-state" networks, known to be involved in distinct aspects of cognition and reward processing. We found that, relative to a placebo, levodopa and haloperidol challenges, respectively, increased or decreased the functional connectivity between (1) the midbrain and a "default mode" network, (2) the right caudate and a right-lateralized frontoparietal network, and (3) the ventral striatum and a fronto-insular network. Further, we found drug-specific associations between brain circuitry reactivity to dopamine modulation and individual differences in trait impulsivity, revealing dissociable drug-personality interaction effects across distinct dopamine-dependent cortico-subcortical networks. Our findings identify possible systems underlying pathogenesis and treatment efficacy in disorders of dopamine deficiency.